2021
DOI: 10.3389/fmed.2021.791715
|View full text |Cite
|
Sign up to set email alerts
|

TELERA—Asynchronous TELEmedicine for Patients With Rheumatoid Arthritis: Study Protocol for a Prospective, Multi-Center, Randomized Controlled Trial

Abstract: Innovative strategies are needed to adequately assess and monitor disease activity of patients with rheumatoid arthritis (RA) in times of scarce appointments. The aim of the TELERA study is to evaluate the feasibility and performance of asynchronous telemedicine visits based on patient-generated data and patient's drug history. RA patients use a medical app, ABATON, that captures the results of a self-performed quick CRP-test, joint-count, and electronic patient-reported outcomes in between visits. This is a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Therefore, we were eager to explore the potential of a new decentralized digitally-supported patient-centered asynchronous RA care-model, and initiated the multicenter TELERA trial [19] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we were eager to explore the potential of a new decentralized digitally-supported patient-centered asynchronous RA care-model, and initiated the multicenter TELERA trial [19] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…It is concluded that the study provides support for the value of implementing Telemedicine in the treatment of rheumatology. 16 …”
Section: Resultsmentioning
confidence: 99%
“…This POC device, QuikRead go [ 20 ], provides exact and fast CRP results, however was not designed for patient use and high costs prevent implementation in routine care. Semiquantitative POC devices, such as those used in the TELERA study [ 21 ], are more affordable, however only indicate ranges of CRP results (i.e., 5–10 mg/l). All of these CRP tests are also based on conventional finger-pricking.…”
Section: Discussionmentioning
confidence: 99%